Implicit Perceptions of Closeness From the Direct Eye Gaze - Cui, Mengmeng; Zhu, Minghao; Lu, Xiaomin; Zhu, Lei (Frontiers in Psychology, 2019)
Eye gaze plays an important role during social interaction. Specifically, different eye gaze direction may send different functional messages to the observers, who have the capacity to automatically interpret these signals. In the present study, we used the implicit association test (IAT) to test whether direct eye gaze sends a functional, automatically perceived signal about non-target interpersonal closeness. Results suggest that the direct gaze strongly signals close relationship, and this association cannot be accounted for by positive valence. The findings suggest that the direct gaze may function to uniquely communicate a generalized closeness without orientation. Discussion focuses on the implications of these findings for social functions of direct gaze during interpersonal interaction and the automatic nature of such associations.